Exploratory factor analysis of post traumatic stress disorder checklist for DSM-5: investigating post traumatic stress disorder interconnected dynamics with depression and anxiety in the aftermath of multiple collective stressors - Josleen Al Barathie; Elie G. Karam (PLoS ONE, 2025)
Post Traumatic Stress Disorder (PTSD), a psychological condition linked to traumatic events, sees continuous Diagnostic Statistical Manual (DSM) criteria adjustments. The PTSD Checklist (PCL-5) is a favored screening tool for its versatility. Exploratory and Confirmatory Factor Analysis (EFA/CFA) studies on PCL-5’s utility across languages and settings reveal varied models, with conflicting outcomes attributed to methodological differences. Prompted by lack of research on PCL-5 in populations exposed to multiple collective traumas, we aim to conduct an EFA among a Lebanese nationally representative sample. To our knowledge, this study represents the first attempt at PCL-5 construct validation in Arabic. Recruitment involved 1,000 Lebanese adults aged 18 +. EFA with Promax rotation, aimed to identify the minimal number of factors among PCL-5 items, supported by Kaiser-Meyer-Olkin (KMO) and Bartlett’s test of sphericity. Eigenvalues above 1 indicate appropriateness for EFA with two retained factors (trauma specific vs non-trauma specific), supported by the scree plot with loadings ranging from 0.532 to 0.775. Understanding PCL-5’s structural factors is crucial, as it directly impacts diagnostic algorithms in clinical and research settings and informs knowledge about PTSD’s comorbidities. This, in turn, affects disorder prevalence, etiology, and intervention formulation. Our paper offers suggestions to tackle PCL-5 performance amidst comorbidity, categorized into DSM and non-DSM related recommendations. DSM-related recommendations include grouping PTSD, depression, and anxiety into a single “distress” disorder or eliminating non-specific PTSD symptoms. Non-DSM-related recommendations propose a shift towards a transdiagnostic approach and advocating for nuanced clinical interviews over self-report questionnaires to address symptom complexity and potential double counting in individuals with significant emotional distress.